The Contest on Mount Carmel (1 Kings 18:19–40) as a Reflection of a Religious-Cultural Threat - Naʾaman, Nadav (Biblische Zeitschrift, 2020)
The article suggests that the story of the contest on Mount Carmel (1 Kgs 18:19-40) is a complete literary unit that was written by a single author in the early Persian period and inserted into the deuteronomistic story-cycle of Elijah. The story is entirely legendary and reflects the polemic of a devotee of YHWH against the contemporaneous spread of the Phoenician cult and culture. The attachment of the story to Mount Carmel may reflect the occasion of the establishment of a Tyrian/Sidonian temple on one of the mountain’s peaks, but this hypothesis cannot be verified. The story conveys a clear religious message of the absolute power of YHWH and the worthlessness of all other gods - in particular the Phoenician God Ba‘al - and of the fallacy of the belief in his divine power.